Postoperative complications of partial inferior turbinectomy vs powered endoscopic turbinoplasty - ALI ABD-ALMER JWAD; WASAM A. ALBUALIH; ABBAS KALAF MAHDI (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background and aims: Nasal obstruction can be induced by various causes; however, inferior turbinate hypertrophy is considered the most frequent cause of this anatomical malfunctioning condition. The current surgical interventional study was focused on comparing the final outcomes of partial inferior turbinectomy (PIT) and powered endoscopic turbinoplasty (PET).Subjects and methods: The criterion followed for deciding the successfulness of each surgical method was the rate of post-operative complication occurrence such as bleeding, crustation, and atrophic rhinitis. Here, 50 patients suffered nasal obstruction were randomly divided into two groups; PIT group, 25 patients, 15 (52%) males and 10 (48%) females, at an average age of 27.40±7.7 years, and PET group, 25 patients, 14 (48%) males and 11 (62%) females, at an average age of 26.68±6.82 years. The surgical operations were performed in the Department of Otolaryngology, Al-Diwaniyah General Teaching Hospital, Diwaniyah City, Iraq, during the period between March, 2015 and March, 2020.Results: The PET group showed significantly (p˂0.05) lower incidence of bleeding and crustation than those from the PIT group; however, no significant (p˃0.05) differences were observed between PIT and PET in the occurrence of atrophic rhinitis.Conclusion: Powered endoscopic turbinoplasty shows promisingly lesser postoperative complications than those from partial inferior turbinectomy.